Situated drinking: The association between eating and alcohol consumption in Great Britain. Issue 3 (June 2023) - Warde, Alan; Sasso, Alessandro; Holmes, John; Hernández Alava, Monica; Stevely, Abigail K.; Meier, Petra S.
Aims: This paper examines the co-occurrence of drinking alcohol and eating in Great Britain. Applying a practice-theoretical framework, it attends primarily to the nature and characteristics of events – to social situations. It asks whether drinking events involving food are significantly different from those without, whether differences are the same at home as on commercial public premises, and whether differences are the same for men and women. The focus is especially on episodes of drinking with meals at home, an infrequently explored context for a substantial proportion of contemporary alcohol consumption.Data: Employing a secondary analysis of commercial data about the British population in 2016, we examine reports of 47, 645 drinking events, on commercial premises and at other locations, to explore how eating food and consumption of alcoholic beverages affect one another. Three types of event are compared – drinking with meals, with snacks, and without any food. Variables describing situations include group size and composition, temporal and spatial parameters, beverages, purposes, and simultaneous activities. Basic sociodemographic characteristics of respondents are also examined, with a special focus on the effects of gender.Results: Behaviours differ between settings. The presence of food at a drinking episode is associated with different patterns of participation, orientations, and quantities and types of beverage consumed. Gender, age, and class differences are apparent.Conclusions: Patterns of alcohol consumption are significantly affected by the accompaniment of food. This is a much-neglected topic that would benefit from further comparative and time series studies to determine the consequences for behaviour and intervention.